Partial purification of toxins HI1, HI2 and HI3 from Hadruroides lunatus Koch, 1867 scorpion venom (Scorpionida : Vejovidae) - Escobar, Enrique (2002)
The proteins from the venom of the scorpion Hadruroides lunatus were separated by ionexchange chromatography on CM-Sephadex C-25 with 0,05M ammonium acetate buffer pH 7, getting six protein peaks in the process. The toxicity tests allowed the identification of three toxins that were denominated Hl1, Hl2 y Hl3; which immobilize, respectively, insects (Grillus sp.), crustaceans (Porcellio laevis) and the inoculated limb of white mice. The three toxins are basic proteins and have no proteolitic or phospholipase activity. In addition, Hl3 increases the plasmatic level of creatine kinase after its inoculation in the gastrocnemius muscle of mice. By PAGE-SDS, Hl3 shows only one protein band of 12,5 KDa, while the other toxins have protein contaminants.